2005
DOI: 10.1158/0008-5472.can-04-2649
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Apoptosis Inhibitor Protein XIAP Contributes to Anoikis Resistance of Circulating Human Prostate Cancer Metastasis Precursor Cells

Abstract: Survival in lymph or blood is an essential prerequisite for metastasis of carcinoma cells to distant organs. Recently, we reported isolation and initial biological characterization of circulating metastatic cells in a fluorescent, orthotopic, metastatic nude-mouse model of human prostate cancer. Here we show that the metastatic human prostate carcinoma cells selected for survival in the circulation have increased resistance to anoikis, which is apoptosis induced by cell detachment. Using gene silencing and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
184
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(193 citation statements)
references
References 38 publications
5
184
0
3
Order By: Relevance
“…Chang and colleagues using model systems showed that around 1×10 6 tumor cells per gram tumor tissue could be introduced daily into the blood stream (Chang et al, 2000). Though 85% CTCs become broken and disappear within 5 minutes, they still could be vital contributors of serum miRNA 200c (Berezovskaya et al, 2005). In other words, higher level of miRNA 200c may represent more tumor cells entering the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Chang and colleagues using model systems showed that around 1×10 6 tumor cells per gram tumor tissue could be introduced daily into the blood stream (Chang et al, 2000). Though 85% CTCs become broken and disappear within 5 minutes, they still could be vital contributors of serum miRNA 200c (Berezovskaya et al, 2005). In other words, higher level of miRNA 200c may represent more tumor cells entering the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, according to the recent studies, variants of prostate carcinoma cells selected for increased metastatic capacity displayed elevated levels of XIAP expression and anoikis resistance when compared to their parental poorly metastatic counterparts. Inhibition of XIAP expression in these cells resulted in the suppression of their anoikis resistance and the ability to metastasize (Berezovskaya et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, nontumorigenic anoikis-susceptible epithelial cells selected for increased anoikis resistance were found to be tumorigenic in vivo (Rak et al, 1999). Finally, treatment resulting in the inhibition of anoikis resistance of diverse types of tumor cells was shown to suppress their in vivo tumorigenicity (Rosen et al, 1998(Rosen et al, , 2000Scotlandi et al, 2002;Duxbury et al, 2004b) and the ability to metastasize (Scotlandi et al, 2002;Duxbury et al, 2004a, b;Jiang et al, 2004;Berezovskaya et al, 2005). For example, we found that ras oncogene blocks anoikis of intestinal epithelial cells by downregulating a proapoptotic protein Bak (Rosen et al, 1998) and by upregulating an antiapoptotic protein Bcl-X L (Rosen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Increased XIAP levels have been linked to escaping anoikis and apoptosis induced by radiation, chemotherapy and death receptor ligands. 13,[17][18][19][20][21][22] Furthermore, antagonism of XIAP has been reported to have antitumor activity in a number of models, including prostate cancer. 21,[23][24][25] Consistent with an antiapoptotic role, high levels of XIAP have an adverse prognosis in certain cancers.…”
mentioning
confidence: 99%